Hand function impairment in Systemic sclerosis: Outcomes, Mechanisms and Experience (HANDSOME) – a longitudinal observational multicentre study protocol - Christopher Denton; Madelon C Vonk; Julia Spierings; Marion Kortekaas; Wouter Foppen; Jeska K de Vries-Bouwstra; Voon H Ong; Simon Mastbergen; Amin Herman; Rita Schriemer; Douwe J Mulder; Paco Welsing; et al. (BMJ Open)
Introduction The majority of all patients with systemic sclerosis (SSc) experience hand function impairment. The exact cause for this impairment is yet unknown. As impaired hand function hugely impacts daily functioning and quality of life, there is a high unmet need for effective treatments. With the availability of new imaging modalities, biomarkers and laboratory techniques, opportunities arise to increase insights into the factors contributing to hand function impairment. The objective of this study is to identify risk factors and underlying mechanisms leading to hand function impairment in SSc.Methods and analysis This is a longitudinal observational multicentre study in patients with very early diagnosis of systemic sclerosis and SSc under care of the Department of Rheumatology and Clinical Immunology of the University Medical Centre Utrecht (UMCU), St Antonius Hospital Nieuwegein, UMC Groningen (UMCG), Leiden UMC (LUMC), Radboudumc or Royal Free Hospital (RFH) London. Patients will be followed for 2 years. Medical history, clinical status, nailfold capillaroscopy, skin assessments, serum biomarker analysis, ultrasound, elastography and MRI will be performed, and results related to hand function measurements will be analysed.Ethics and dissemination This study was approved by the Medical Research Ethics Committee NedMec (MREC NedMec) in the Netherlands and by HRA and Health and Care Research Wales in the UK. Results will be published in scientific journals and presented at scientific congresses and patient meetings.Trial registration number NCT06133244.Protocol version V1.3 6-06-2024.